2009
DOI: 10.1016/j.otsr.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Frohse's arcade is not the exclusive compression site of the radial nerve in its tunnel

Abstract: Anatomic studies have revealed a variable rate of occurrence of a tendinous AF, which range from 30 to 80% (87% in our study) according to authors. It is reported to be a predisposing factor to the development of chronic entrapment neuropathy of the DBRN, especially if it is thick and provides a narrow opening for passage of the DBRN. The tendinous consistency of the supinator arch is believed to develop in adults, in response to repeated rotary movements of the forearm. Repetitive pronation and supination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 17 publications
2
48
1
5
Order By: Relevance
“…It is important to consider the variability of the pattern of radial nerve innervation at the distal level, as we have been able to observe in our study [1,11,12]. This explains the three pareses of the common finger extensors seen in our patients caused by excessive distal dissections.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…It is important to consider the variability of the pattern of radial nerve innervation at the distal level, as we have been able to observe in our study [1,11,12]. This explains the three pareses of the common finger extensors seen in our patients caused by excessive distal dissections.…”
Section: Discussionsupporting
confidence: 51%
“…There are no alterations in the normal static neurophysiological state with a normal nerve conduction velocity [3,5,6,9,10,[13][14][15]. This is all due to the fact that the PIN is compressed intermittently by the muscles that form the radial tunnel, causing pain [6,11,12,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have supported the involvement of the extensor muscles of the wrist, particularly the extensor carpi radialis brevis muscle, in LE. 21,22,53,54 Clavert et al 15 observed in an anatomical study that the radial nerve may get entrapped in the superolateral aspect of the extensor carpi radialis brevis muscle. Therefore, it is possible that impairments in this muscle can lead to mechanical irritation of the radial nerve.…”
Section: Peripheral Nerve Nociception and Central Sensitizationmentioning
confidence: 99%
“…The most common cause of radial tunnel syndrome is entrapment by the arcade of Frohse, a fibrous arch within the superficial head of the supinator (76,92). Other sites of entrapment include fibrous bands arising between the joint capsule and brachioradialis, vascular arcades of the recurrent radial artery known as the leash of Henry, or under the leading edge of the extensor carpi radialis brevis (76,92,93).…”
Section: Radial Nervementioning
confidence: 99%